High Vapor Pressure Deficit Decreases the Productivity and Water Use Efficiency of Rain‐Induced Pulses in Semiarid Ecosystems. Issue 10 (26th September 2020) - Roby, Matthew C.; Scott, Russell L.; Moore, David J. P.
Abstract: Intermittent rain events drive dynamic pulses of carbon and water exchange in many arid and semiarid ecosystems. Although soil moisture is known to control these pulses, the effect of atmospheric dryness on pulses is not well documented. Here we hypothesized that vapor pressure deficit ( VPD ) modulates net ecosystem production ( NEP ) and ecosystem‐scale water use efficiency ( WUE ) during pulse events due to its effects on canopy stomatal conductance and evapotranspiration. We quantified relationships between VPD and carbon and water exchange during growing season rain events and tested their generality across four semiarid flux sites with varied vegetation in the southwest United States. Across grassland, shrubland, and savanna sites, we found that high VPD during pulses suppressed ecosystem photosynthesis and surface conductance to a greater degree than respiration or evapotranspiration, particularly when soil moisture was high. Thus, periods of high VPD were associated with a 13–64% reduction in NEP and an 11–25% decrease in WUE, relative to moderate VPD conditions. Sites dominated by shrubs with the C3 photosynthetic pathway were more sensitive to VPD than sites dominated by C4 grasses. We found that a 1 kPa increase in VPD reduced the average NEP of pulse events by 13–56%, which illustrates the potential for projected increases in atmospheric demand to reduce the net productivity of semiarid ecosystems. Plain Language Summary: In many water‐limited regions, summer storms provide water that drives brief periods of high ecosystem activity (photosynthesis, respiration, and evapotranspiration) called "pulse events". While many studies have focused on soil moisture as a control on pulse events, it is not well known how changes in the air's evaporative strength, or dryness, influence patterns of carbon and water exchange during pulses. We analyzed data from four semiarid sites in southern Arizona and found that air dryness modified the widely accepted pulse framework of carbon and water exchange for semiarid areas. Drier air led to larger reductions in photosynthesis than respiration and evapotranspiration, which decreased the overall productivity and water use efficiency of plants. These findings indicate the potential for drier air in a warming climate to reduce the ability of dryland plants to use water. Because pulses are important for the carbon balance of these systems, drier during these critical pulse periods could reduce how much carbon global drylands remove from the atmosphere. Incorporating the effects of air dryness on pulse patterns into models may help us better understand global change impacts on semiarid ecosystems. Key Points: We extend the pulse framework of carbon and water exchange in semiarid ecosystems to include atmospheric demand for moisture High atmospheric demand drove larger reductions in photosynthesis than respiration, which decreased the net productivity and water use efficiency of rain pulses Ecosystem photosynthesis was most sensitive to high atmospheric demand in sites dominated by C3 shrubs when soil moisture was high